Quality of Life Assessment in Retinoblastoma: A Cross‐Sectional Study of 122 Survivors from India. Issue 2 (21st October 2015) - Batra, Atul; Kumari, Mamta; Paul, Reeja; Patekar, Mukesh; Dhawan, Deepa; Bakhshi, Sameer
Abstract : Background: With current modalities, cure rates of retinoblastoma are high and hence the number of survivors is increasing. However, data on quality of life (QOL) are minimal. Procedure: We analyzed QOL in 122 retinoblastoma survivors using the PedsQL TM 4.0 generic core scale. The self‐reported questionnaire was filled by children of more than 5 years of age who had completed treatment for more than 12 months. The questionnaire consists of 23 questions on physical, social, emotional, and school domains on a scale from 0 to 4. This was converted to a scale from 0 to 100, where higher values represented better QOL. The QOL was compared with 50 siblings. Factors predicting the QOL were assessed. Results: The median age of retinoblastoma survivors was 98 months (range 60–247) and 68% were males. Overall QOL was significantly poorer in retinoblastoma survivors as compared with the controls. The emotional health domain of QOL was significantly affected. Difficulties in maintaining friendships and competing were reported in the social health domain. The school health domain showed significantly higher absenteeism. However, the physical health domain, including household work, exercise, and self‐care, was similar in both the groups. Lower age at diagnosis (≤18 months) predicted better QOL ( P = 0.05), whereas age at assessment, sex, IRSS stage, and previous surgery and radiotherapy were not predictive of poor QOL. Conclusions: We found a significantly poorer QOL in retinoblastoma survivors with the psychosocial health domain being more affected than the physical domain. Age less than 18 months at diagnosis predicted better QOL.